2020
DOI: 10.3390/insects11070430
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of Locally Recruited Egg Parasitoids of the Fall Armyworm in Africa

Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is an insect native to the tropical and subtropical Americas that has recently spread to Africa, where it predominately attacks maize, sorghum and other plant species. Biological control is an environmentally friendly way of combatting the pest and contributes to an integrated pest management approach. In Africa, several trichogrammatid parasitoids and Telenomus remus Nixon (Hymenoptera: Platygastridae) have been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 70 publications
3
20
1
Order By: Relevance
“…The presence of T. remus in Uganda offers promise for the control of FAW eggs. Indeed, T. remus was identified as an effective parasitoid of FAW eggs capable of causing 64% and 78% parasitism in the field and screenhouse in Niger [ 71 ], respectively, and is known to occur in several other African countries [ 38 ]. Because of its occurrence in Africa, emphases should be placed on conducting more distribution, effectiveness, and mass production studies, rather than exploring options for importation into Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of T. remus in Uganda offers promise for the control of FAW eggs. Indeed, T. remus was identified as an effective parasitoid of FAW eggs capable of causing 64% and 78% parasitism in the field and screenhouse in Niger [ 71 ], respectively, and is known to occur in several other African countries [ 38 ]. Because of its occurrence in Africa, emphases should be placed on conducting more distribution, effectiveness, and mass production studies, rather than exploring options for importation into Africa.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first published study outside the native range of the pest describing trials in farm conditions and assessing the impact on naturally occurring FAW populations during two maize growing seasons. The authors of [21] conducted field trials in sorghum in Niger, but these were carried out in much smaller plots (200 m 2 ) and parasitism was assessed on sterile eggs exposed in plots for four days only. From the few publications describing field tests in the Americas, nearly all used small experimental plots with sentinel eggs exposed close to the release points, which makes comparisons with our study very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Americas have shown that augmentative releases of T. remus in maize fields can result in high parasitism rates on sentinel egg masses of S. frugiperda [17][18][19] and such releases have been conducted on a large scale in Venezuela [20]. However, except one study that assessed the parasitism rate of T. remus on sentinel FAW egg masses in Africa [21], little is known about the real potential of T. remus to control FAW under ecological conditions and agricultural systems and practices in Africa. We aimed to address this knowledge gap by conducting replicated field release trials with T. remus for FAW control in large maize plots in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need to develop new, more sustainable approaches to FAW management. Alternative control measures are being considered including the use of biopesticides 6 , biological control [7][8][9] , and agroecological practices such as intercropping with legumes, push-pull system, and diversifying the farm environment [10][11][12] . The choice and scaling of these alternative solutions depend on accurate characterization of the potential permanent and temporal distribution of FAW across the continent as well as how FAW and the agriculture production system will respond to a changing climate.…”
Section: Introductionmentioning
confidence: 99%